Management and Appropriate Technology Catfish Cultivation and Food Processing at the Groups of Elok Mekar Sari SME’s Surabaya - Mujanah, siti; Ruben, Nayve; Sumiati, Sumiati; I Dewa Ketut Raka, Ardiana; Sucahyani, Cicik Ari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This Community Service (PKM) activity aims to increase productivity, business efficiency, and economic added value at the Elok Mekar Sari Surabaya MSME through the application of Appropriate Technology (TTG) and innovation in catfish-based products. The main problems faced by partners include limitations in water quality management, high fish mortality rates, and low product diversification and business management. The method used in this activity is a participatory approach through the stages of preparation, implementation, mentoring, and monitoring and evaluation. The implementation of technology includes the use of a 1200-liter water tank, water pumps, filtration systems, aerators, and the application of a biofloc system to maintain water quality. In addition, innovations in processing catfish products into shredded fish and nuggets were carried out to increase added value. The results of the activity showed an increase in more stable water quality, a decrease in fish mortality rates, and an increase in cultivation productivity. Furthermore, there was an increase in the partners' business management capacity through more structured financial records, business planning, and cost analysis. Product diversification also provides opportunities for increasing income and expanding the market. Overall, this PKM activity has a positive impact on economic and social aspects, and encourages the sustainability of businesses based on local potential.